THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSETS, AND COMPANY SIZE ON STOCK PRICE (EMPIRICAL STUDY ON PHARMACEUTICAL COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2017 - 2021) - Debby Novi Indrianti; Ivo Rolanda (Universitas Budi Luhur, 2023)
The average value of share prices in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2017-2021 shows a change in the average share price in 2017 of 2,082.20, then decreased in 2018 to 1,922.30. In 2019 it decreased again to 1,588.40, then in 2020 it increased to 4,705.90 and in 2021 it started to decline again to 3,402.20, so it can be interpreted that stock prices are always changing. Changes in the share price are influenced by investor considerations in purchasing shares based on the performance of the company's financial statements. This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, Return on Assets, and Company Size on Share Price in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2017 - 2021. The samples of this study were 9 pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2017-2021. This research was conducted using multiple linear regression methods with the help of the SPSS version 25 and Microsoft Excel 2016 programs. The results showed that Current Ratio, Debt to Equity Ratio, and Return on Assets had no significant effect on stock prices, while company size had a significant effect on stock prices.